Career Decision Making at Class XII Islamic Boarding School Darul Hijrah Putra Martaputa - Yasa Widhi Asta Pramana; Ghozali Rusyid Affandi (Proceedings of The ICECRS, 2020)
This research is motivated by the phenomenon of class XII students in determining career decision making. This study aims to determine the career decision making for santi class XII Darul Hijrah Putra Martapura Islamic Boarding School. This research is a descriptive quantitative research. The variable contained in this study is career decision making. This research was conducted at the Darul Hijrah Putra Islamic Boarding School with a population of 221 students. the sample in this study were 139 students based on the error level of 5% in the table developed by Isaac and Michael taken using simple random sampling technique. Data collection techniques in this study use a psychological scale with a Likert scaling model that is the scale of career decision making. Data analysis was performed using descriptive statistical techniques with the help of Microsoft Excel calculations. The results of data analysis showed (19%) students had low career decision making, while students who had moderate career decision making (65%) students and students who had high career decision making (16%) students. This is also supported by the highest average value in the aspect of career understanding of 43.86 where most of the students have good career understanding, while the lowest average value in the aspect of career information is 42.1 so that Darul Hijrah Putra Martapura Islamic Boarding School needs provide career information services for students